Australia's 'war on terror' discourse - Gleeson, Kathleen (Ashgate Publishing Routledge, 2014)
Too often, existing literature has conflated the discourses that enabled the 'War on Terror', ignoring the contextual specificities of the states that make up the 'Coalition of the Willing'. Australia's 'war on terror' Discourse fills this gap by providing a full and sustained critical analysis of Australian foreign policy discourse along with the theoretical synthesis for a specific model of critical discourse analysis of the subject